TINJAUAN YURIDIS DEFECTOR 38TH PARALLEL MILITARY DEMARCATION LINE SEMENANJUNG KOREA - Mikail Aditia Rahman (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Mikail Aditia Rahman, Herman Suryokumoro, Yasniar RachmawatiFakultas Hukum Universitas BrawijayaJl. MT. Haryono No. 169 MalangEmail : mikailaditia@gmail.comAbstract Defector is a common subject found when studying history or politics of Korean Peninsula, a region still engulfed in war to date. The term defector refers to migration or desertion. The issue concerning defector in North Korea went global on 13 November 2017, where Oh Chong-song (24 years old back then), a North Korean Soldier, crossed the 38th Parallel Demarcation Line in Panmunjom. The desertion of Oh was witnessed by South Korea and Oh was seen to have managed to go across the border by a military jeep. This issue escalated desertion in Korean Peninsula, where desertion is seen as treachery or asylum. The research result has learned that there is a legal loophole over desertion in International Humanitarian Law, which has caused overlapping interpretation and legislation concerning the status and protection of deserters. It is essential that this legal loophole be resolved by International Humanitarian Law to avoid implication, misinterpretation, and violation of law in the future. Keywords : Defector, Deserter, International Humanitarian Law. Abstrak Defector atau pengkhianat, subjek yang umum ditemukan dalam mengkaji sejarah dan politik di Semenanjung Korea, wilayah yang hingga saat ini masih dalam keadaan â€œperangâ€. Istilah defector ni merujuk pada migrasi atau desersi. Isu defector Korea Utara kemudian mendunia pada 13 November 2017 silam, dimana Oh Chong-song (kala itu 24 Tahun) seorang tentara Korea Utara â€œberkhianatâ€ melintasi Zona Demiliterisasi 38th Parallel di Panmunjom. Desersi Oh disaksikan oleh pihak Korea Selatan dimana pada hari itu terlihat Oh berhasil melintasi perbatasan dengan sebuah jeep militer. Hal ini kian mewarnai perkara desersi di Semenanjung Korea, yaitu bagaimana desersi dilihat sebagai sebuah pengkhianatan, atau suaka. Hasil dari penelitian ini menunjukkan terdapatnya kekosongan hukum mengenai desersi dalam Hukum Humaniter Internasional, yang mengakibatkan tumpang-tindihnya interpretasi dan legislasi akan status dan perlindungan desertir. Menjadi sebuah urgensi bagi Hukum Humaniter Internasional untuk mengatasi kekosongan hukum seputar desersi, guna menghindari terjadinya implikasi, misinterpretasi, dan pelanggaran hukum di masa yang akan datang. Kata Kunci : Desertir, Pengkhianat, Hukum Humaniter Internasional.